A poesia de Cecília Meireles na sala de aula: a criação poética como expressão escrita dos alunos do 6º ano - Silva, Claudevânia Santos de Menezes (2021)
This work aims to subsidize pedagogical practices that can contribute to the development of reading and writing skills in 6th grade students of the Municipal School Frei Cristóvão de Santo Hilário, located in the city of Lagarto-SE. The material used in the teaching / learning process will be poetry by Cecília Meireles, taken from her work OU ISTO OU AQUILO published in the year of her death, in 1964. These poems will be motivating texts for the poetic creation of the students, mainly, regarding themes covered in the referred work for children and youth, such as: childhood, grandmother's house, imagination, the world under the eyes of a child, among other themes of the children's universe. Thus, the activities designed to carry out this project aim to sensitize students through the textual genre poetry and immerse them in the universe of reading and writing, with an emphasis on the poetic creation of students. And, as a contribution to the Professional Master's Program in Letters, produce a pedagogical notebook with a didactic sequence proposal that helps the Elementary School teacher in the application of Cecília Meireles literature in the classroom with a view to the reader training and the development of the students' writing. For the development of this project we rely on the theoretical support of the following writers:Rildo Cosson (2019); Neusa Sorrenti (2013), Hélder Pinheiro (2018); Antônio Cândido (1987); Tzvetan Todorov (2009), in previous dissertations by Almeida (2018), Araújo (2018), among other authors.